(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to enhance the digital creativity of students at SMA Negeri 1 Semarapura through training in digital storytelling techniques and video editing using the CapCut application. The program is motivated by the significant potential of the creative industry for Generation Z; however, there remains a gap in skills related to producing structured and engaging video content. The program involved 37 students and was conducted through an interactive workshop consisting of theoretical lectures on narrative concepts, technical demonstrations of CapCut features, and guided hands-on practice in creating short videos. Evaluation using the Kirkpatrick Model showed a success rate of 91.6%, indicating a significant improvement in students’ digital literacy and storytelling skills. Participants were not only able to operate technical editing features such as transitions and audio adjustments, but also capable of integrating strong storytelling structures into their work. Overall, this training effectively equipped students with practical and relevant skills to prepare them for future opportunities in the digital creative industry.